2017
DOI: 10.1007/s12350-015-0354-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of coronary CT angiography vs stress cardiac imaging in patients following hospital admission for chest pain work-up: The Prospective First Evaluation in Chest Pain (PERFECT) Trial

Abstract: Randomization of hospitalized patients admitted for chest pain work-up to either CCTA or to stress testing resulted in similar discharge times, change in medical therapies at discharge, frequency of downstream noninvasive testing, and repeat hospitalizations. However, a higher frequency of invasive coronary angiography and revascularization procedures were performed in the CCTA arm. (ClinicalTrials.gov number, NCT01604655.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The included studies were heterogeneous in terms of the symptomatic status, modality of functional testing, and follow‐up duration (Table ). Among the total included studies, 7 RCTs investigated the impact of CCTA strategy in patients with acute chest pain: the Coronary Computed Tomographic Angiography for Systematic Triage of Acute Chest Pain Patients to Treatment (CT‐STAT) trial, the CT Coronary Angiography Compared to Exercise ECG (CT‐COMPARE) trial, the CATCH trial, the Prospective Randomized Outcome Trial Comparing Radionuclide Stress Myocardial Perfusion Imaging and ECG‐gated CCTA (PROSPECT), the Prospective First Evaluation in Chest Pain (PERFECT) trial, the study by Faisal Nabi et al, and the ACRIN‐PA 4005 trial . Five RCTs enrolled patients with stable chest pain: the Cardiac CT for the Assessment of Pain and Plaque (CAPP) trial, the Computed Tomography vs Exercise Testing in Suspected Coronary Artery Disease (CRESCENT) trial, the PROMISE trial, the SCOT‐HEART trial, and the International Atomic Energy Agency (IAEA)‐SPECT/CTA study .…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were heterogeneous in terms of the symptomatic status, modality of functional testing, and follow‐up duration (Table ). Among the total included studies, 7 RCTs investigated the impact of CCTA strategy in patients with acute chest pain: the Coronary Computed Tomographic Angiography for Systematic Triage of Acute Chest Pain Patients to Treatment (CT‐STAT) trial, the CT Coronary Angiography Compared to Exercise ECG (CT‐COMPARE) trial, the CATCH trial, the Prospective Randomized Outcome Trial Comparing Radionuclide Stress Myocardial Perfusion Imaging and ECG‐gated CCTA (PROSPECT), the Prospective First Evaluation in Chest Pain (PERFECT) trial, the study by Faisal Nabi et al, and the ACRIN‐PA 4005 trial . Five RCTs enrolled patients with stable chest pain: the Cardiac CT for the Assessment of Pain and Plaque (CAPP) trial, the Computed Tomography vs Exercise Testing in Suspected Coronary Artery Disease (CRESCENT) trial, the PROMISE trial, the SCOT‐HEART trial, and the International Atomic Energy Agency (IAEA)‐SPECT/CTA study .…”
Section: Resultsmentioning
confidence: 99%
“…Combining these results in a meta-analysis, these authors showed that a strategy of initial coronary CTA resulted in greater use of further downstream testing and coronary angiography compared to initial testing with either MPI or exercise ECG (24.4% vs. 18.5%; OR 1.38, 95% CI 1.33-1.43; P  = 0.0001). The tendency for patients evaluated initially by CCTA to increase the likelihood of downstream coronary angiography (and revascularization) has also been observed in the context of low-risk patients with acute chest pain 19,20. However, a more recent randomized trial comparing exercise ECG with CCTA in patients with stable chest pain showed a greater use of downstream non-invasive testing in the exercise ECG arm 21.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative clinical effectiveness of cardiac tests has been the focus of numerous studies recently due to both an increasing number of cardiac imaging and escalating healthcare costs 15. CCTA has been one of the most promising modalities extensively studied in both observational studies and clinical trials 1.…”
Section: Discussionmentioning
confidence: 99%